Process Evaluation of an Implementation Trial: Design, Rationale, and Early Lessons Learnt From an International Cluster Clinical Trial in Intracerebral Hemorrhage - Ouyang, Menglu; Anderson, Craig S.; Song, Lili; Malavera, Alejandra; Jan, Stephen; Cheng, Guojuan; Chu, Honglin; Hu, Xin; Ma, Lu; Chen, Xiaoying; You, Chao; Liu, Hueiming (Frontiers in Medicine, 2022)
Background: The third INTEnsive care bundle with blood pressure Reduction in Acute Cerebral Hemorrhage Trial (INTERACT3) is an ongoing, international, multicenter, stepped-wedge cluster, prospective, randomised, open, blinded endpoint assessed trial evaluating the effectiveness of a quality improvement ‘care bundle’ for the management of patients with acute spontaneous intracerebral hemorrhage (ICH) in low- and middle-income countries (LMICs). An embedded process evaluation aims to explore the uptake and implementation of the intervention, and understand the context and stakeholder perspectives, for interpreting the trial outcomes. Methodology: The design was informed by Normalisation Process Theory and the UK Medical Research Council process evaluation guidance. Mixed methods are used to evaluate the implementation outcomes of fidelity, reach, dose, acceptability, appropriateness, adoption, and sustainability, as well as relevant contextual factors and mechanisms affecting delivery of the care bundle. Semi-structured interviews and non-participant observations are conducted with the primary implementers (physicians and nurses) and patients/carers to explore how the care bundle was integrated into routine care. Focus group discussions are conducted with investigators and project operational staff to understand challenges and possible solutions in organisation of the trial. Data from observational records, surveys, routine monitoring data, field notes and case report forms, inform contextual factors and adoption of the intervention. Purposive sampling of sites according to pre-specified criteria is used to achieve sample representativeness. Discussion: Implementation outcomes, and relevant barriers and facilitators to integrating the care bundle into routine practice, will be reported after completion of the process evaluation. The embedded process evaluation will aid understanding of the causal mechanisms between care bundle elements and clinical outcomes within complex health systems across diverse LMIC settings.